Anxiety assessment in Nursing students: integrative literature review (Research, Society and Development, 2021)
To identify the elements that make up the assessment of anxiety in nursing students. Integrative literature review, with the guiding question: “What elements make up the assessment of anxiety in students attending higher education in nursing?”. Searches were performed in the following databases: LILACS, PubMed, Scopus, Web of Science, CINAHL and SciELO. 46 studies comprised the review; of these, 95.6% used instruments and 8.7% used clinical signs and symptoms to assess anxiety. The most frequent instruments were the State-Trait Anxiety Inventory (STAI); the Depression, Anxiety and Stress Scale (DASS-21); and, clinical signs and symptoms: changes in breathing, heart rate, body temperature and presence of nervousness. This review contributes to the advancement of research related to anxiety in nursing students. It is suggested, however, to carry out studies with higher levels of evidence involving the elements of anxiety assessment, especially with regard to clinical signs and symptoms.